271 Survival outcomes of patients with clear cell carcinoma cervix: a single institutional retrospective analysis. (4th December 2020) - Sudhakaran, Akhilesh CS; Kumar, Aswin; James, Francis; Mathews, Susan; Joseph, John
Abstract : Introduction/Background: Cervical cancer is the most prevalent cancer and the fifth most common cause of cancer death in Indian women. Clear cell carcinoma of the cervix (CCCC) is rare, accounting for only 4% of all adenocarcinomas. CCCC can occur sporadically or in association with in-utero diethylstilbestrol (DES) exposure. There are no clear-cut treatment recommendations for the management of CCCC. Early-stage disease is usually treated by surgery and more locally advanced stages by chemoradiation followed by brachytherapy. Methodology: Aim: This study aimed to assess the survival outcomes and patterns of failure of patients with CCCC. Settings and Design : Retrospective study done at Regional Cancer Centre, Thiruvananthapuram, Kerala, India Material and Methods : Case records of all the patients with CCCC who were diagnosed and treated between 1995 and 2015 were reviewed for clinical, pathological and treatment characteristics. Statistical analysis : Disease-free survival (DFS) and overall survival (OS) were estimated using the Kaplan-Meier method. Results: The diagnosis of clear cell carcinoma of the cervix was confirmed in 15 patients. The median age was 53 years. 20% of the patients were in the International Federation of Gynaecology and Obstetrics (FIGO) stage I, 60% in stage II, 7% in Stage III and 13% in stage IVA. Stage IB and IVA patients were managed surgically, and adjuvant therapy decided based on the tumour pathology. Stage IIB and IIIB patients were treated with concurrent chemoradiation followed by brachytherapy. The median follow-up period was 47 months. The three-year DFS and OS were 13.3% and 13.3% respectively. Conclusion: CCCC has a poor prognosis, stage for stage compared to other histologies. The FIGO stage, tumour size, lymphovascular space invasion and pelvic node status were factors that predicted the prognosis. Adjuvant radiotherapy or chemoradiotherapy have a limited role in the treatment of this rare cancer. Disclosures: The authors have no potential conflict of interest to disclose.